2023
DOI: 10.1103/physrevmaterials.7.034001
|View full text |Cite
|
Sign up to set email alerts
|

Stacking domain morphology in epitaxial graphene on silicon carbide

Abstract: Terrace-sized, single-orientation graphene can be grown on top of a carbon buffer layer on silicon carbide by thermal decomposition. Despite its homogeneous appearance, a surprisingly large variation in electron transport properties is observed. Here, we employ aberration-corrected low-energy electron microscopy to study a possible cause of this variability. We characterize the morphology of stacking domains between the graphene and the buffer layer of three different high-quality samples to capture the range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…The soliton length of about a M = 250 nm gives an estimate of εbi=(anormalbanormalt)/at=aGr/aM0.1%${\varepsilon}_{\mathrm{bi}}=({a}_{\mathrm{b}}-{a}_{\mathrm{t}})/{a}_{\mathrm{t}}={a}_{\mathrm{Gr}}/{a}_{\mathrm{M}}\approx 0.1\%$ where a t = a Gr is the lattice constant of the top layer assumed to be unstrained and a b is the lattice constant of the bottom layer. This value is consistent with previous measurements [ 26–28 ] which concluded that strain is imposed to the bottom layer by the 63×63R30$6\sqrt {3}\times 6\sqrt {3}R30^\circ$ SiC reconstruction.…”
Section: Resultssupporting
confidence: 93%
“…The soliton length of about a M = 250 nm gives an estimate of εbi=(anormalbanormalt)/at=aGr/aM0.1%${\varepsilon}_{\mathrm{bi}}=({a}_{\mathrm{b}}-{a}_{\mathrm{t}})/{a}_{\mathrm{t}}={a}_{\mathrm{Gr}}/{a}_{\mathrm{M}}\approx 0.1\%$ where a t = a Gr is the lattice constant of the top layer assumed to be unstrained and a b is the lattice constant of the bottom layer. This value is consistent with previous measurements [ 26–28 ] which concluded that strain is imposed to the bottom layer by the 63×63R30$6\sqrt {3}\times 6\sqrt {3}R30^\circ$ SiC reconstruction.…”
Section: Resultssupporting
confidence: 93%